Discovery of Polyoxypregnane Derivatives From Aspidopterys obcordata With Their Potential Antitumor Activity - Guo, Hong-Wei; Tian, Yun-Gang; Liu, Yi-Han; Huang, Jia; Wang, Jian-Xia; Long, Hua; Wei, Hua (Frontiers in Chemistry, 2022)
The bioassay-guided phytochemical study of an ethnic medicinal plant Aspidopterys obcordata led to the isolation of ten new polyoxypregnane derivatives, named aspidatasides A-H (1-8), along with ten known analogues (9-18). All the isolated were tested for their cytoxic activity against HL-60 cells, and compound 2 showed the highest potency with an IC50 8.03 μM. Preliminary structure-activity relationship studies displayed that the sugar chain and double bond could notable impact their biological activity.